Do women in rural areas of Serbia rarely apply preventive measures against cervical cancer? - Antić, Ljiljana; Djikanović, Bosiljka; Vuković, Dejana; Kaludjerović, Vladimir (Vojnosanitetski pregled, 2014)
Background/Aim. The incidence of cervical cancer in Central Serbia has the higher rate as compared with that in other European countries. Considering mortality rate for cervical cancer, the standardized rate in Serbia is 10.1 per 10,000 females, which is the second highest one after that in Romania with 13.0. The aim of this study was to examine application of preventive measures for cervical cancer in women both from rural and urban areas in Serbia and if they are associated with sociodemographic characteristics and sexual behaviour. Methods. We analyzed secondary data of the 2006 National Health Survey of the population of Serbia focused on characteristics of adult females aged 25 to 65 years (5.314 in total) taking into consideration that programme of the organized screening will include female population aged over 25 years. Results. Respondents from rural areas have gynecological examination less than once a year in comparison with those from urban areas (OR = 0.60, 95% Cl 0.54–0.68). Less women from rural areas did Pap test during the last 12 months in comparison with respondents from urban areas (OR = 0.55, 95% Cl 0.48–0.64). Respondents from urban areas less often do the Pap test on doctor's advice in comparison with those from rural one (OR = 0.55, 95% Cl 0.42–0.62). Conclusion. This study shows that women in rural areas rarely implement preventive gynecological measures againt cervical cancer in comparison with those in urban areas. Implementation of preventive measures among rural women is conditioned by lower levels of education and lower socioeconomic status.
Keywords: uterine cervical neoplasms; rural health; urban health; vaginal smears; socioeconomic factors; women; serbia